The Existence of Sell in May and Go Away in ASEAN-5 - Sholihati, Naila 'Ainaya; Nuansari, Shindy Dwita (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research aims to test the existence of Sell in May and Go Away in the ASEAN-5 market. This quantitative research was conducted from May 2013 to October 2023 on the five founding countries of ASEAN. The dynamic panel data regression approach with the Generalized Method of Moment (GMM) estimation system which includes the unit root test, sargan test, and Arellano-Bond test with the help of Stata software. This research shows that the November-April period positively affect stock returns. This research found that there was Sell in May and Go Away in 4 of 5 ASEAN countries. This research also found that the January effect cannot strengthen the positive relationship between the November-April period and stock returns.